PENGARUH POSISI KERJA TERHADAP KEJADIAN LOW BACK PAIN PADA PEKERJA DI KAMPUNG SEPATU, KELURAHAN MIJI, KECAMATAN PRAJURIT KULON, KOTA MOJOKERTO - Kusuma, Irawan Fajar; Hartanti, Ragil Ismi; Hasan, Muhammad (IKESMA, 2014)
Low Back Pain is the main symptom on the report it to health practitioners associated with decreased work productivity. Low Back Pain associated with frequent lifting, carrying, pushing and pulling of heavy goods, frequent or long to bend the body, bending, sitting or standing for long or other body posture is not natural. standing in the long term, the body can only tolerate stood with one position only for 20 minutes. If more than these limits, the elasticity of the tissue will decrease gradually and finally the pressure increased and muscle discomfort arises on the back. The ergonomics work positions be a deciding factor of occurrence of Low Back Pain. This research aims to know the influence of the working position of the genesis of Low Back Pain, and compare the influence of two working positions (standing and seated) against the occurrence of Low Back Pain. Based on data results showed that job position does have an impact on incidence of Low Back Pain. Evidenced by the results of the statistical test of Chi Square Test Crosstab values X2 count or value of the Pearson Chi-Square Test is 8,480 and the Degree of Freedom (df) is worth 3. And the value of Asymp. Sig (2-sided) is 0,037. The second comparison results analysis of the position of sitting and standing work, then both positions workÂ  standing or sitting equally had a significant influence on the incidence of Low Back Pain. However, when compared in more detail, seated position has the more influence than the standing position , it can be proved by the results of Chi Square Test Crosstab, the value of X2 count on higher seating position work i.e. 14,267 compared with 13,467 standing work position. Keywords: working position, low back pain, ergonomy